ANALISIS PENGARUH LAVERAGE TERHADAP PROFITABILITAS PERUSAHAAN YANG TERMASUK LQ45 PERIODE AGUSTUS 2015 – JANUARI 2016 DI BURSA EFEK INDONESIA - Endah Dewi Purnamasari (Universitas Indo Global Mandiri)
This study aims to analyze the effect of Leverage and profitability on companies that include LQ 45 in Indonesia Stock Exchange (BEI). The independent variable in this research is Leverage (X), while the dependent variable is profitability (Y). This study uses secondary data of public companies listed on the Indonesia Stock Exchange. Data taken in this research is information about DER, DAR, ROA and ROE. The sampling technique used in this study is purposive sampling with Company criteria included in LQ 45 in period August 2015 - January 2016 and have company data from year 2010-2015. The data analysis technique with the method of analysis with Structural Equation Modeling (SEM) and its model is measured by Second Order Confirmatory Factors Analysis (2ndCFA). For analysis tools using SmartPLS software. Based on the results of hypothesis testing using Path Coefficients Profitabitas = - 0.1266 Leverage which says that leverage has a significant negative effect on profitability. Meanwhile, based on the outer loadings, it is suggested that the most influential construct variable is the debt to equity ratio (DER).Key words : Leverage, profitability, LQ 45, DER, DAR, ROA and ROE